IMPROVING PEDAGOGICAL APPROACHES TO DEVELOPING POSITIVE ATTITUDES TO FAMILY VALUES IN STUDENTS - Axmedov Aminjon Amrullayevich (Scholars Digest Publishing, 2024)
This article explores the importance of fostering positive attitudes toward family values in students and examines innovative pedagogical approaches to achieve this goal. Emphasizing respect, responsibility, empathy, and cooperation, family values are essential in shaping individuals who can contribute meaningfully to society. The article discusses the role of schools and teachers in nurturing these values and highlights various effective strategies, such as integrating values into the curriculum, experiential learning, role-playing, positive reinforcement, parental involvement, and mentorship programs. Case studies from different countries illustrate the successful implementation of these approaches. Despite challenges, the integration of family values into education is crucial for developing well-rounded individuals capable of positively impacting society.
Keywords: Family values, education, pedagogy, primary education, respect, responsibility, empathy, cooperation, curriculum integration, experiential learning, role-playing.